Косметична олія для очищення шкіри - Носенко, Т. Т.; Волощенко, Т. О.; Сідоренко, Т. В. (НТУ "ХПІ", 2015)
Проведені дослідження по створенню косметичної олії для очищення шкіри, зокрема, створення композиції з рослинних олій із урахуванням фізіологічної дії рослинних олій, їх жирнокислотного складу, рекомендованих співвідношень жирних кислот. Розроблено рецептури жирових композицій, максимально наближені до рекомендованого співвідношення жирних кислот (олеїнова : лінолева, лінолева : ліноленова) для різних типів шкіри. В рецептурах косметичного засобу використано олію із насіння бузини, одержану в лабораторних умовах, яка є цінним джерелом поліненасичених жирних кислот та каротиноїдів. Визначено вміст каротиноїдів у косметичній олії.

Researching for creation of cosmetic oil for skin cleaning was carried out in this work. In particular, vegetable oil compositions were created on the basis of their physiological effect, fatty acids composition and recommended ratio of main fatty acids. Designed formulations of fat compositions maximally approximated to recommended ratios of main fatty acids (oleic : linoleic, linoleic : linolenic). The main oils for dry skin were sunflower higholeic oil, containing about 84 % oleic acid, and rape oil which contains α-linolenic acid. Apricot and grape seed oil, jojoba and almond oils were predominated in fat formulations for normal skin type. The laboratory obtained oil from Sambucus nigra seeds was also included in oil compositions. It was abounded on polyunsaturated fatty acids - linoleic and α-linolenic acid. The content of carotenoids was determined in cosmetic compositions too. These pigments increase the regeneration of skin epithelium due to their antioxidant properties. The sources of carotenoids in designed formulations were Sambucus and rape oils. Thus, the formulations of new cosmetic oils that can be used for skin cleaning were designed in this study.
Cosmetic oil for skin cleaning
Keywords: кислоти жирні; олія рослинна; полісорбат-20; кромоллент; олія ефірна; fatty acids; vegetable oil; polysorbate-20; cromollent; essential oils